Undocumented immigrants and mental health: A systematic review of recent methodology and findings in the United States - Luz M. Garcini; Ryan Daly; Nellie Chen; Justin Mehl; Tommy Pham; Thuy Phan; Brittany Hansen; Aishwarya Kothare (Elsevier, 2021)
This study reviewed the methodology and findings of 44 peer-reviewed studies on psychosocial risk factors associated with mental health outcomes among undocumented immigrants (UIs) in the United States. Findings showed a considerable advancement over the past seven years in the methods and measures used in the included studies. Nonetheless, there is a need for continued methodological rigor, innovative study designs, greater diversity of samples, and in-depth exploration of constructs that facilitate resilience. Identifying avenues to reduce risk in this population is essential to inform intervention and advocacy efforts aimed at overcoming distress from the current U.S. anti-immigrant and socio-political climate.